Local perceptions of ecosystem services in protected areas in Eastern Burkina Faso - Ouedraogo, Issaka; Sambare, Oumarou; Savadogo, Salfo; Thiombiano, Adjima (Ethnobotany Research and Applications, 2020)
Background: Ecosystems provide countless services to humans. However, the source of ecosystem services is poorly understood, leading to serious conservation problems. This study aims to assess local perceptions of ecosystem services and their source of supply. Methods: It was carried out in three protected areas and their surrounding areas in eastern Burkina Faso. Semi-structured individual interviews were conducted with nearly 148 people to identify the benefits they derive from protected areas (PA) and local strategies for their sustainability. The benefits have been classified between the four categories of ecosystem services (provisioning, regulation, cultural and support) and another category called “other services”. Citation percentages were calculated and a statistical comparison test was performed. A Principal Component Analysis was also conducted to distribute the different benefits by PA. Results: The local populations listed eight protected areas offering 39 types of benefits, distributed among the different categories. The procurement services category and the "other services" category provide the maximum number of services. The benefits offered vary from one area to another. The W national park offers the most benefits (64.10%). The conservation status of each protected area influences the provision of services. Thus, most of the services classified by the Millennium Ecosystem Assessment are provided by parks while those in the “other services” category are provided by hunting areas. People recognize ecosystem services with their sources of supply and have proposed 25 solutions to ensure their sustainability. Conclusion: Local people have provided important data that can help in the development of reliable management plans taking into account their cultural knowledge and aspirations. Keywords: Conservation, Local populations, Sustainable management of natural resources, Ecosystem services, Local strategies